(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ustadi, Ikhsan N, Junus M, Suyadi. 2021. Improving the larvae acceptance rate and morphometric characteristics of queen Apis cerana javana by grafting larvae at different ages. Biodiversitas 23: 166-170. This study was aimed to evaluate the effect of different ages of grafted larvae on the acceptance rate and morphometric characteristics of queen Apis cerana javana Fabr. The total of 72 larvae were 1, 2, and 3 days old and was reared in 7 colonies with 3 treatments (larvae age) and 6 replications. The morphometrics studied consisted of body length, emergence weight, head length, head width, thorax length, thorax width, fore wing length, fore wing width, abdomen length, and abdomen width. The results showed that the different ages of grafted larvae had a highly significant on body length, emergence weight (P<0.01), significant on abdomen length (P<0.05), but not on head length, head width, thorax length, thorax width, fore wing length, fore wing width, abdomen width, acceptance rate. However, the higher acceptance rate was 73.33% to be found in 1 day old of larvae than in 2 and 3 days old. The age of grafted larvae of 1 day old has a higher body length, emergence weight, and abdomen length (P<0.05) than in 2 and 3 days old of larvae. Thus, it can be concluded that the age of grafted larvae of 1 day old was the best age to queen rearing of Apis cerana javana.